Training Public Health Professionals to Tackle Women, Children, and Families Health Issues: A “Skill-Based Qualitative Learning Approach” - Obeng, Cecilia (Frontiers in Public Health, 2021)
Purpose: There are several teaching and learning approaches but finding the one that is appropriate for a particular field or training program is an arduous task. The purpose of this paper is to introduce the “Skill Based Qualitative Learning Approach” (SBQLA) in training health professionals. Description: The SBQLA is a pedagogical approach via which learners are trained in developing qualitative questionnaires and interview skills to learn from experts in the Public Health (PH) field. This teaching approach arms a student with interview skills that help them identify and address PH roadblocks and get them authentic information from experts. It also equips them with techniques on how to do formalized presentations and come up with projects and interventions that help mitigate and eliminate drivers of health problems among women, children and families Assessment: Learners’ field experiences are shared in a professional presentation style in a class to help trainees benefit from each other’s information and to get formalized feedback on their presentation. Assessment in this learning approach is based on a synthesis and an analysis of data collected from professionals. Conclusion: Findings from this learning approach enables experts to shed light on true stories shared by real and authentic individuals whose faces can be associated with their shared experiences. This learning approach makes it possible for trainees to also initiate projects that help them tackle existing and emerging public health issues in their future work.